NILAI DAN VEKTOR EIGEN MATRIKS INTERVAL ATAS ALJABAR MAX-PLUS - M, Dwi Suci; suryoto., Suryoto (MATEMATIKA, 2009)
An interval matrix A with given  and  is the set of all matrices  such that . Eigenvalue and eigenvector of A is called possible eigenvalue and eigenvector of an interval matrix